(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Chronic diffuse liver diseases (CDLD) are one of the most common and clinically significant pathologies in gastroenterology and hepatology [1,3]. Long-term inflammatory and destructive processes in the liver lead to gradual restructuring of the parenchyma, the formation of fibrosis, and then cirrhosis, which in some cases is complicated by the development of hepatocellular carcinoma (HCC) [2]. In this regard, non-invasive radiation diagnostic methods are of particular importance, allowing for a timely assessment of morphological changes, determining the stage of the process and identifying signs of malignancy [4,5].